Vaccination With Live Attenuated Vaccines in Four Children With Chronic Myeloid Leukemia While on Imatinib Treatment - Bettoni da Cunha-Riehm, Claudia; Hildebrand, Verena; Nathrath, Michaela; Metzler, Markus; Suttorp, Meinolf (Frontiers in Immunology, 2020)
Chronic myeloid leukemia (CML) in childhood and adolescence is a rare malignancy that can successfully be treated with the tyrosine kinase inhibitor (TKI) imatinib. According to the current experience, treatment is necessary for years and, in the majority of cases, a lifelong approach is required to control the malignant disease. To what extent imatinib causes immunosuppression in different age cohorts is a controversial discussion. According to general medical recommendations, live vaccines are contraindicated in individuals treated with imatinib. However, a recent increase in the number of globally reported cases of measles has been observed and continues to rise. Due to the high contagiousness of the virus, near-perfect vaccination coverage (herd immunity of 93 to 95%) is required to effectively protect against measles resurgence—a scenario that is not realistic in many countries. When four teenagers with CML (median age 13 years, range 12–15) who were enrolled into pediatric trial CML-paed II while on imatinib treatment (median treatment duration 36 months, range 11–84) were identified without protective measles and/or varicella titers, we carefully balanced the risks of a live vaccination under immunosuppressive TKI medication against the benefit of being protected. The patients underwent live vaccination with the live attenuated vaccines M-M-RVAX Pro® and Varivax® simultaneously (Patient #1), Priorix® and Varilix® consecutively (Patient #2), and Priorix® (Patients #3 and #4). While the first three patients were vaccinated while receiving TKI therapy, treatment with imatinib was interrupted in patient #4 for 1 week prior and 2 weeks after vaccination. Patients #1 and #3 reacted with stable long-term seroconversion. In Patient #2, serum titer conversion against measles and varicella could not be demonstrated and thus revaccination with Priorix® and Varilix® was performed 3 years later. However, protective titers did not develop or were lost again. Patient #4 also lost protective titers against measles when assessed 10 months after vaccination, but revaccination resulted in stable seroprotective titers over 12 months after the last vaccination during ongoing imatinib treatment. We conclude that in all patients, the safety of live vaccines could be documented, as no acute or late adverse events were observed. However, in line with observations that memory B-cells are lost under exposure to imatinib, revaccination may become necessary (two out of four patients in this small series lost their seroprotection). Considering that the number of cases is very small, we also suggest some criteria for decision-making regarding live vaccinations of CML patients treated with imatinib.